Molecular Detection and Genotyping of Enterocytozoon bieneusi in Black Goats (Capra hircus) in Yunnan Province, Southwestern China - Shi-Chen Xie; Yang Zou; Zhao Li; Jian-Fa Yang; Xing-Quan Zhu; Feng-Cai Zou (Animals, 2021)
Enterocytozoon bieneusi is a fungus-like protist that can parasitize in the intestines of humans and various animals causing a threat to public health. However, there has been no data for E. bieneusi prevalence and genotypes in black goats in Yunnan Province, Southwestern China. In this study, 907 fecal samples were collected from black goats in 5 counties from Yunnan Province. The prevalence and genotypes of E. bieneusi were examined by nested PCR amplification targeting the nuclear internal transcribed spacer (ITS). Multi-locus sequence typing (MLST) was used to further examine the potential occurrence of genetic segregation. The overall prevalence of E. bieneusi in black goats in Yunnan Province was 10.3% (93/907). Statistical analysis revealed that E. bieneusi prevalence was significantly associated with the region, age and gender of black goats (p < 0.001). Four new genotypes (CYG-1, CYG-2, CYG-3, CYG-4) and 11 known genotypes (CHG1, CHG2, CHG3, CHG5, CHG28, J, D, BEB6, Wildboar3, CD6, SDD1) of E. bieneusi were identified. At the microsatellite and minisatellite loci, 15, 2, 17, and 33 sequences were obtained, respectively, forming one new multi-locus genotype (MLG27). Phylogenetic analysis revealed that all 15 genotypes were clustered into group 1 and group 2, with zoonotic potential. This is the first report of E. bieneusi prevalence and genotypes in black goats in Yunnan Province, China. Effective control strategies and measures should be taken to reduce the risk of E. bieneusi transmission between black goats, other animals, and humans.